(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In the article views at essence of God, religion, belief in the light of comparative on the basis of analysis of L.N.Tolstoy`s «Book of reading» and Abay`s «Book of words». The author gives an explanation of Tolstoy`s and Abay`s religion views existential character. In consist: that they are concentrated round a problem of the person, sense of his life and mission. The other display of Tolstoy`s and Abay`s reasonings` existential direction, to the author’s opinion is aspiration to achive is not only through the mind, but also through the judgment of feeling and experiences. The author proves that religious searches of great thinkers are connected with doubts and attempt to conﬁ rm a reasonable belief in an everyday life of the person. The article shows an importance of true belief in the statement of good, mercy, justice in human relations. The author has opened originality and novelty of the religious doctrine of L.N.Tolstoy`s and Abay`s, has shown their accord which consists in that they not only stand up for belief, religion, love for God, but also express conﬁ dence that the morals can`t became a real support to the person in life if it isn`t supplemented and shined with personal belief in God.